Spray Drying of Honey: The Effect of Drying Agents on Powder Properties - Samborska Katarzyna; Gajek Paulina; Kamińska-Dwórznicka Anna (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to investigate the possibility of honey spray drying with addition of maltodextrin and gum Arabic as drying agents. The influence of the concentration of the solution subjected to drying, the type and content of the drying agents upon the physical properties of obtained powders was examined. An attempt was undertaken to obtain powder with a honey content of more than 50% d.b. Spray drying of multifloral honey with the addition of maltodextrin and gum Arabic was carried out at inlet air temperature of 180°C, feed rate of 1 mL/s and rotational speed of a disc atomizer of 39,000 rpm. The properties of obtained powders were quantified in terms of moisture content, bulk density, Hausner ratio, apparent density, hygroscopicity and wettability. Using gum Arabic it was possible to obtain a product with a higher content of honey (67% solids) than in the case of maltodextrin (50% d.b.). However, the powders obtained with gum Arabic were characterised by worse physical properties: higher hygroscopicity and cohesion, and longer wetting time.